Genotype detection of fimH gene of Acinetobacter baumannii isolated from different clinical cases - Rana M. Abdullah; Rasha Z. Ahmed (مجلة مركز بحوث التقنيات الاحيائية, 2019)
Background: Forty isolates were obtained of Acinetobacter baumannii from (200) samples, the samples were collected from different cases including: - wounds, burns, Stool, Urinary tract infection urine.